The Challenges of Improving ELT Students ' Motivation in Speaking Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Motivating English language learners to participate actively in speaking activities continues to pose a significant challenge for English language teachers worldwide, especially in contexts where English is not spoken outside the classroom. This article examines the persistent barriers to speaking motivation, drawing on up-to-date research and the practical experiences of a non-native English teacher. The paper identifies cultural factors, classroom anxiety, insufficient communicative practice, and teacher-related issues as key obstacles. It offers practical, research-supported strategies for overcoming these barriers, including scaffolded speaking tasks, meaningful topics, positive error correction, and contextually appropriate group dynamics. The aim is to help EFL teachers encourage even reluctant learners to speak more confidently and fluently.